Global and local feature fusion via long and short-term memory mechanism for dance emotion recognition in robot - Lyu, Yin; Sun, Yang (Frontiers in Neurorobotics, 2022)
In recent years, there are more and more intelligent machines in people's life, such as intelligent wristbands, sweeping robots, intelligent learning machines and so on, which can simply complete a single execution task. We want robots to be as emotional as humans. In this way, human-computer interaction can be more natural, smooth and intelligent. Therefore, emotion research has become a hot topic that researchers pay close attention to. In this paper, we propose a new music emotion recognition based on global and local feature fusion method. If the single feature of audio is extracted, the global information of music cannot be reflected. And the dimension of data features is very high. In this paper, an improved long and short-term memory (LSTM) method is used to extract global music information. Linear prediction coefficient is used to extract local information. Considering the complementarity of different features, a global and local feature fusion method based on discriminant multi-canonical correlation analysis is proposed in this paper. Experimental results on public data sets show that the proposed method can effectively identify music emotion compared with other state-of-the-art emotion recognition methods.